A survey of energy harvesting circuits: research issues and challenges. - Jiménez Pérez, David; Guerra Gómez, Rolando; Torres Gómez, Jorge (Telemática, 2016)
Energy Harvesting is referred to the capability of collecting ambient energy. Circuits has been designed for recovering energy from several sources: radio frequency (RF) signals, thermal energy, kinetic motion and mechanical vibration for naming a few. This solution applies to self-powered devices just like power charging, remote environment monitoring, mobile devices, health and structural monitoring. This paper addresses the circuits implemented for RF energy harvesting. This circuits harvest energy from Digital Television towers, Mobile Networks (GSM) and Wireless LAN. In this paper, the general block scheme is presented and the circuit elements are discussed in detail. Besides some figures of merits like efficiency conversion and output power are illustrated. The practical applications for powering some electronics devices is also analyzed. Finally, some research issues and challenges are also described.